Assessment of Factors Influencing Adherence to Antidiabetic Drugs among Patients with Type 2 Diabetes Mellitus at a Tertiary Care Hospital in India - Nandini H C; Akshay Gali; Sushma Muraraiah (Pharmacology and Clinical Pharmacy Research)
Diabetes mellitus is a chronic endocrine disorder that requires long-term treatment. Non-adherence to anti-diabetic drugs is common and associated with poor outcomes. Non-adherence leads to complications, higher incidence of hospital admissions and imposes economic burden. Hence, the present study was undertaken to measure adherence to anti-diabetic medication and factors contributing to it. This cross-sectional study was conducted among patients on anti-diabetic medication after taking their informed consent in a tertiary care hospital in India. Each patient’s demographic, clinical, and treatment data along with the adherence to treatment has been assessed during a personal interview with each patient using Medication Adherence Report Scale (MARS-5). Factors contributing to medication adherence was assessed using chi-square test. A total of 250 patients were recruited in the study. The mean age was 54 years and non-adherence to anti-diabetic medications was 21.6%.  Univariate Analysis showed that marital status, education status, good glycemic control, illness >5years had a statistically significant association (p=<0.05) with self-reported adherence to anti-diabetic medication.